Effectiveness of dietary intervention in geriatric patients receiving new complete dentures: A randomized controlled trial - Sheetal Vijaya; Anisha Rodrigues; Meenakshi Garg; Shilpa Vijaya; Meghan J. Shetty; Shradha Dhanania (Wolters Kluwer Medknow Publications, 2024)
Aim: This study aimed to evaluate the effectiveness of a tailored progressive dietary intervention against the standard care instructions on the nutritional status and nutrient intake in geriatric patients receiving new complete dentures. Settings and Design: Randomized controlled trial. Materials and Methods: A randomized controlled trial was conducted on completely edentulous patients seeking complete dentures. The participants were randomly allocated into two groups, and each group received a separate set of advice. The cognitive function was assessed using the mini-mental state examination (MMSE) form. The outcome measures were assessed at the baseline and 3 months after denture insertion. The Mini Nutritional Assessment (MNA) form was used to evaluate the nutritional status and the nutrient intake was calculated by a 3-day 24-h dietary recall and fed into the DietCal software. Statistical Analysis Used: The analysis was done using the independent sample t-test, paired sample t-test, and analysis of co-variance. The significance level was set at 0.05 for all tests. Results: In total, 68 participants completed the trial. There were no significant differences in food intake between the two groups at baseline. However, at 3-month follow-up, the intervention group displayed a statistically significant improvement in body mass index (BMI) compared to the control group. Although the nutrient intake such as protein, dietary fiber, total fat, calcium, carbohydrate, energy, iron, and Vitamin B12 was higher in the intervention group than in the control group, it was not statistically significant. Conclusion: Simple, tailored dietary intervention with prosthetic restoration of the edentulous patients significantly improved BMI and MNA scores.